Scripture, Time, and Authority among Early Disciples of Christ. Issue 4 (26th January 2017) - Perry, Seth
Abstract : This article explores the relationship between the idealization of the Bible and the material characteristics of printed bibles among the Disciples of Christ in the early nineteenth century. The Disciples were founded on the principles of biblical primitivism: they revered the "pure" Bible as the sole source for proper faith and practice. The tenacity with which Disciples emphasized their allegiance to an idealized, timeless Bible has obscured their attention to its physical manifestations and use as printed scripture. The timeless authority of the Bible was entangled with the historical contingencies of mere bibles, and the ways in which they dealt with these tensions offer important perspective on nineteenth-century bible culture. Scholars have treated primitivism as an ahistorical impulse—the idealization of the New Testament church as a mythical sacred era outside of time that could be perpetually inhabited. By contrast, through an examination of the New Testaments edited and published by Disciples leader Alexander Campbell and the heavily-annotated preaching bible of Thomas Allen, an early Disciples preacher, I argue that in seeking to recover the New Testament era through historicized understandings of scripture, primitivists like Campbell and Allen situated the early church itself firmly within historical, not primordial, time.